Comparative evaluation of antibacterial effects of Nd : YAG laser irradiation in root canals and dentinal tubules - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
The antibacterial effects of the Nd:YAG laser on contaminated root canals and dentinal tubules were observed as the aim of this study, The samples were inoculated with Streptococcus sanguis (NCTC 7853) and Prevotella intermedia (NCTC 93336), and the effects of Nd:YAG laser were tested on these teeth. The specimens were lased with 1.8 W and 2.4 W Nd:YAG laser for 30 s, and the presence of bacteria in tubules was observed under light microscopy, The 1.8 W laser sterilized the tubules in 86.3% of sections inoculated with S, sanguis, whereas 2.4 W laser sterilized in 98.5% of the sections. Both laser powers sterilized ail samples inoculated with P, intermedia. The scanning electron microscopic observations supported the light microscopic findings.
Keywords: DENTISTRY; RADIATION